La vivencia de los cuentos fantásticos y su incidencia en el desarrollo de la creatividad en los niños y niñas del primer año de educación básica del centro educativo Sagrado Corazón de la ciudad de Loja periodo 2013 - Gonzaga Abad, Jessica Isabel (2015)
This present study is limited in the analysis of "THE EXPERIENCE OF FANTASTIC TALES AND ITS IMPACT ON THE DEVELOPMENT OF CREATIVITY IN CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL SACRED HEART OF THE CITY OF PERIOD 2013 Loja". It is theoretical-descriptive. Aims. Raise awareness of the importance of the story in the development of creativity, working with children in creating fantastic stories of their personal experiences acquired. Sacred Heart School in the city of Loja. Took place with the participation of 22 people, of whom 19 were children and three teachers at the school. To perform this research work using the following methods, scientific, analytical-synthetic and inductive, deductive and also apply the instrument of a survey of teachers to know what methodology used in teaching reading, and use resources and observation sheet for children to see if they have creativity to make a story or try to imagine. After analyzing the information obtained from teachers and children came to the conclusion that the influence of fairy tales is more prevalent in women, that 80% of children we applied the test has six years of chronological age, which important is the habit of reading for the child's reading development, and the development of their creativity. It is recommended that children who have little interest at the time of the narrative of a fantasy tale get extra help from the teachers of the institution, and help foster the habit of reading, that from the age of 6 must be developed reader learning, and to be given adequate attention to children to prevent disorders that affect their lives.